Male pattern hair loss: Taking one for the team: The selfless gene. (May 2018) - Uzoigwe, Chika Edward; Sanchez Franco, Luis Carlos; Gascon Conde, Ignacio; Sanchez Campoy, Adrian
Abstract: Male pattern hair loss (MPHL) is exceedingly common. It is characterised by onset in early adulthood and progression with age. It has a strong heritable component. The reason for its existence remains unexplained. Given that MPHL is progressive and has its earliest manifestations in young adults it may be a barometer of age. Here we suggest that MPHL may have atavistically allowed women in our species and ancestor species to select younger (but not necessarily the youngest) adult mates. Evidence suggests that conceptions by younger fathers are more likely to lead to live births and less likely to result in miscarriage. Further children fathered by younger men may have improved health and be less likely to suffer from a number of co-morbidities. This is collectively known as the "paternal age affect". Hence the selection of younger males mediated by the MPHL may improve the fitness of the population and of the species at the expense of the individual. Indeed MPHL may have been an evolutionary "nudge" directing women to favour younger partners. It is conceivable that for a species whose success is predicated upon co-operation, collaboration and altruism the gene cannot be exclusively selfish and must have a selfless allele.